Online Learning During the Covid-19 Pandemic: Reflection on Self-Efficacy of Primary School Teachers in Teaching Online - Wahyuni, Esa Nur; Mangestuti, Retno; Maimunah, Iffat; Aziz, Rahmat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
One of the critical variables in the online learning process during the Covid-19 pandemic is teachers' self-efficacy to their ability to carry out online learning. However, the fact is not all teachers have the efficacy of teaching online. The article invites readers to reflect by analyzing the causes of low self-efficacy of elementary school teachers carrying out online learning. The study used a mixed-method approach involving 22 elementary school teachers. Primary and secondary data collection using questionnaires, interviews, observations, and documentation. Data analysis used quantitative and qualitative. The results show that three factors cause low self-efficacy of elementary school teachers: first, teachers' perception that online learning is ineffective and efficient; second, weak mastery and skills to apply technology for learning; and thirdly, the lack of online learning support facilities during the pandemic. This study's results can be an empiric basis for improving teachers' quality by schools, communities, and governments, especially related to online learning, not only during the Covid-19 pandemic but also in the long run education in the digital age.